Pengaruh Variasi Trietanolamin terhadap Evaluasi secara Fisik Sediaan Krim Body Scrub dari Serbuk Belimbing Wuluh (Averrhoa bilimbi Linn) - Senya Puteri Amalia; Rianita Meilinda; Erma Septiani; Priscilla Harviana Damayanti; Muhammad Hafizh Abiyyu Fathin Fawwazi; Desy Ayu Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Body scrub is a type of cosmetic preparation that has seen increased use, particularly with the incorporation of natural ingredients as its base. Belimbing wuluh (Averrhoa bilimbi Linn.) is a traditional medicinal plant known for its high content of saponins, flavonoids, tannins, glycosides, and formic acid, all of which contribute to its significant antioxidant activity. This makes it a promising candidate for development into a cosmetic product for skin care. This study involved the formulation of body scrub preparations using A. bilimbi powder, with variations in triethanolamine (TEA) as an emulsifying and alkalizing agent to optimize the resulting product formula, which was then tested physically. The A. bilimbi fruit was processed into simplicia, which was subsequently ground and formulated into three different body scrub formulas. These three formulas were subjected to organoleptic tests, homogeneity tests, and pH tests to assess the impact of varying TEA concentrations. The results indicate that TEA influences the texture and pH values of the body scrub preparations. However, the distribution of the preparations based on the homogeneity test results showed no significant differences among the three formulas. The study identified Formula II, with a 3% TEA concentration, as the most optimal formula, meeting SNI standards for pH and demonstrating the best organoleptic properties among the three formulas.